Improving Students’ Critical Thinking through Guided Discovery Learning Method in Argumentative Texts Reading - Henny Dwi Iswati; Oikurema Purwati (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
To effectively satisfy the 21st century learning capabilities, students' critical thinking abilities must be improved, especially in higher education. When learning to read, this can be performed. In this instance, the students should employ their critical reading strategies. students can employ critical reading practices to develop their critical thinking abilities. In this study, an argumentative text was chosen since students in higher education should be able to write scientific papers like theses and journal articles. This study aims to apply the Guided Discovery Learning method in critical reading classes using argumentative texts. This research was conducted on third semester students of the English Education study program, Surabaya State University. Data collection was obtained through observation, tests, and questionnaires. The results of the study show that the reading of argumentation texts becomes more in-depth and critical after the Guided Discovery Learning method is applied. This increase is partly due to the existence of elements of experience and concrete situations that make it easier for students to understand problems and make decisions in a comprehensive manner. Keywords: Critical Thinking, Guided Discovery Learning, Argumentative text.